DAMPAK E-COMMERCE TERHADAP PENDAPATAN PEDAGANG PASAR TRADISIONAL MADURA: PENDEKATAN TEORI DISINTERMEDIASI EVANS DAN WUSTER - Sugiyanto Romadhon; Khofidhatur Rafiah S; Haflatul Kamila; Yudistira; Farahdilla Kutsiyah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study employed a quantitative research method involving 40 traditional market traders in Madura as respondents. Data were collected through questionnaires using Likert and ratio scales. The results indicate that disintermediation and its mechanisms jointly have a significant effect on the income of traditional market traders. This is evidenced by the R Square value of 0.513, which shows that the two variables explain 51.3% of the variation in traders' income, while the remaining 48.7% is influenced by other factors outside the scope of this study. Furthermore, the F-test result shows a significance value of 0.000 < 0.05, indicating that the model is statistically significant. The t-test results reveal that the richness variable has a negative and significant effect on traders' income, whereas the reach variable has a positive and significant effect on traders' income.